Desarrollo de una ración práctica para la alimentación de pollos. I. Uso de harinas de algodón y ajonjolí - BRESSANI, R.; Casas P, I.A. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Several experiments with New Hampshire chicks were carried out to evaluate the nutritional quality of a ration prepared with ingredients available in the Central American area. Sesame and cottonseed oil meals, alone or in different combinations, were used as the protein source, meals of several forages as the source of carotene, a commercial mixture as the source of minerals and blood meal as the source of lysine and animal protein. The results showed that cottonseed meal alone or combined with sesame oil meal on a 50 percent basis gave the best feed conversion values. The substitution of part of the corn for buckwheat resulted in a lower feed conversion but the addition of small amounts of meat scraps or of skim milk did not improve further the nutritional quality of the ration. The results indicate that it is possible to prepare a simplified ration for growing chicks with native products to the Central American area, as long as the ingredients of the ration, especially the protein source, are of high nutritional value.